2018
DOI: 10.1002/jcp.27249
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potency of pharmacological adenosine receptors agonist/antagonist on cancer cell apoptosis in tumor microenvironment, current status, and perspectives

Abstract: The hypoxic niche of tumor leads to a tremendous increase in the extracellular adenosine concentration through alteration of adenosine metabolism in the tumor microenvironment (TME). This consequently affects cancer progression, local immune responses, and apoptosis of tumor cells. Regulatory effect of adenosine on apoptosis in TME depends on the cancer cell type, pharmacological characteristics of adenosine receptor subtypes, and the adenosine concentration in the tumor niche. Exploiting specific pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…We also detected the tumor metastasis–related matrix metalloproteinases (MMPs) and found that adenosine increased MMP-2, MMP-7, MMP-9, and MMP-13 expression in the MKN45 cells, but that SCH 58261 blocked this effect (Figure 2D). However, the expression of MMP9, 48 h and 72 h decreased slightly more than 24 h, which may be related to adenosine-induced tumor cell apoptosis (Sargazi et al , 2019; Soleimani et al , 2019). Collectively, these findings demonstrate that adenosine promotes tumor invasion and metastasis in GC through the A2aR pathway.…”
Section: Resultsmentioning
confidence: 95%
“…We also detected the tumor metastasis–related matrix metalloproteinases (MMPs) and found that adenosine increased MMP-2, MMP-7, MMP-9, and MMP-13 expression in the MKN45 cells, but that SCH 58261 blocked this effect (Figure 2D). However, the expression of MMP9, 48 h and 72 h decreased slightly more than 24 h, which may be related to adenosine-induced tumor cell apoptosis (Sargazi et al , 2019; Soleimani et al , 2019). Collectively, these findings demonstrate that adenosine promotes tumor invasion and metastasis in GC through the A2aR pathway.…”
Section: Resultsmentioning
confidence: 95%
“…It is well known that escape from apoptosis is the basis of cancer pathogenesis, and apoptosis drives cancer cells proliferate and metastasize [17]. Apoptosis involves a series of biochemical events, which are mediated by a variety of cellular signals [18]. On the one hand, Caspase3 is a major executioner caspase, active Caspase3 degrades multiple cellular proteins and is responsible for cell morphology changes and DNA fragmentation during apoptosis [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the four Ado receptors in apoptosis of cancer cells has been reported and reviewed recently [71,72]. Apoptosis can occur through A1 [73,74,75], A2A [76,77,78], A2B [79,80], and A3 [81,82,83,84,85,86,87,88,89] receptors (Figure 3).…”
Section: Adenosine Deaminasementioning
confidence: 94%